The ultrastructure of the midgut epithelium in millipedes (Myriapoda, Diplopoda) - Sosinka, A; Rost-Roszkowska, M M; Vilimova, J; Tajovský, K; Kszuk-Jendrysik, M; Chajec, Ł; Sonakowska, L; Kamińska, K; Hyra, M; Poprawa, I (Arthropod structure & development, 2014)
The midgut epithelia of the millipedes Polyxenus lagurus, Archispirostreptus gigas and Julus scandinavius were analyzed under light and transmission electron microscopies. In order to detect the proliferation of regenerative cells, labeling with BrdU and antibodies against phosphohistone H3 were employed. A tube-shaped midgut of three millipedes examined spreads along the entire length of the middle region of the body. The epithelium is composed of digestive, secretory and regenerative cells. The digestive cells are responsible for the accumulation of metals and the reserve material as well as the synthesis of substances, which are then secreted into the midgut lumen. The secretions are of three types - merocrine, apocrine and microapocrine. The oval or pear-like shaped secretory cells do not come into contact with the midgut lumen and represent the closed type of secretory cells. They possess many electron-dense granules (J. scandinavius) or electron-dense granules and electron-lucent vesicles (A. gigas, P. lagurus), which are accompanied by cisterns of the rough endoplasmic reticulum. The regenerative cells are distributed individually among the basal regions of the digestive cells. The proliferation and differentiation of regenerative cells into the digestive cells occurred in J. scandinavius and A. gigas, while these processes were not observed in P. lagurus. As a result of the mitotic division of regenerative cells, one of the newly formed cells fulfills the role of a regenerative cell, while the second one differentiates into a digestive cell. We concluded that regenerative cells play the role of unipotent midgut stem cells.
Keywords: Millipedes; Midgut epithelium; Digestive cells; Regenerative cells; Stem Cells; Arthropods; členovci; kmenové buňky; Animals; epitel; Epithelium; Česká republika; Secretory cells; trávicí systém; Digestive System; zvířata; Czech Republic; Ultrastructure